Sustained Clinical Response of Pseudotumoral Lesion of the Central Nervous System in Behcet's Disease After Treatment with Infliximab. Case Report. - Bruno Bidin Brooks Joseph; César Prosdócimi Fábio; André Oliveira Rodrigo; Lopes da Silveira Guilherme (Journal of Clinical Case Reports and Images, 2020)
This case documents a pseudotumoral CNS lesion in Behcet's disease with sustained response to infliximab therapy. Clinical evolution, neuroimaging changes, and rationale for TNF‑alpha inhibition are detailed. The report supports considering biologic therapy for refractory neuro‑Behcet manifestations under specialist guidance.
Keywords: Behcet disease